PENGARUH INTERAKSI GURU–SISWA TERHADAP HASIL BELAJAR IPS DENGAN MOTIVASI BELAJAR SEBAGAI VARIABEL INTERVENING PADA SISWA KELAS VII UPTD SMP NEGERI 4 PEMATANGSIANTAR T.A. 2025/2026 - Desry Sapta Aglesi Tarigan; Herlina Hotmadinar Sianipar; Susy Alestriani Sibagariang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the influence of teacher-student interaction on learning outcomes through learning motivation as an intervening variable in seventh-grade students at the UPTD of SMP Negeri 4 Pematangsiantar in the 2025/2026 academic year. Using a quantitative approach with path analysis, data were collected through questionnaires and documentation, then processed using SPSS 26. The results showed that teacher-student interaction had a positive and significant effect on learning motivation (R-square = 0.320). Furthermore, teacher-student interaction and learning motivation simultaneously had a strong influence on learning outcomes (R-square = 0.704). Based on hypothesis testing and the Sobel test, learning motivation was found to significantly mediate the effect of teacher-student interaction on learning outcomes. In conclusion, the more effective the interaction between teachers and students, supported by high learning motivation, the more optimal the learning outcomes achieved by students. This demonstrates the importance of pedagogical and psychological aspects in improving academic achievement.